Home-range size and movement patterns of Hooded Vultures Necrosyrtes monachus in southern Africa. (2nd January 2019) - Reading, Richard P; Bradley, James; Hancock, Peter; Garbett, Rebecca; Selebatso, Moses; Maude, Glyn
Abstract : Hooded Vulture Necrosyrtes monachus populations have declined dramatically in recent years, but we know little about their ecology. We radio-tagged four vultures in northern Botswana to gather data on animal movement and home-range patterns. Hooded Vultures were primarily sedentary at night. Hooded Vultures moved similar distances and speeds during the wet and dry season, and travelled over similar home ranges as measured using minimum convex polygons (MCP), but used much smaller core areas during the dry (breeding) season. We found significant differences in mean distances and speeds moved among different birds, and when comparing day to night, but not between the wet (non-breeding) and dry (breeding) season or by year. All of the variables we tested, including individual vulture differences, season, year and number of fixes, significantly influenced 95% MCP and kernel density estimate (KDE) home-range sizes. Hooded Vultures used significantly smaller KDE home-range sizes during the dry (breeding season) than in the wet (non-breeding) season. Hooded Vultures travelled smaller daily distances over smaller home ranges than most other vulture species for which data exist.